A Method for Shortening of the Rat Spine and its Neurologic Consequences. (1993) - de Medinaceli, Luis; Wyatt, Richard Jed
Abstract : Large laboratory animals are the usual choice for complex surgical procedures on the spine and spinal cord, such as shortening of the spine. It would, however, be advantageous to be able to use a small inexpensive mammal like the rat. We describe a procedure which allows thoracic spondylectomy (T8-T9) to be performed in the rat with a satisfactory survival rate (69%). Functional consequences of the procedure on animals with uninjured spinal cord were monitored over a period of six months, at which time histologic examination was performed. There was a good correlation between operative trauma, consisting of mechanical injury to the cord assessed from the surgical notes, and the duration of postoperative spinal shock. Animals for which the cord appeared laminated or deformed at the time of sacrifice tended to show incomplete functional recovery. Cord cavitation developed, in most surviving animals (78%) but did not have a measurable adverse effect on functional outcome. In the present study, the cord was not intentionally injured; however, availability of this procedure may facilitate the future development of methods to implement recovery of function following spinal cord injury.